Assessment of 10‐year changes in liver stiffness using vibration‐controlled transient elastography in non‐alcoholic fatty liver disease. Issue 8 (23rd May 2019) - Nogami, Asako; Yoneda, Masato; Kobayashi, Takashi; Kessoku, Takaomi; Honda, Yasushi; Ogawa, Yuji; Suzuki, Kaori; Tomeno, Wataru; Imajo, Kento; Kirikoshi, Hiroyuki; Koide, Tomoko; Fujikawa, Hirotoshi; et al.
Abstract : Aim: Although liver biopsy is the gold standard for the diagnosis and staging of non‐alcoholic fatty liver disease (NAFLD), repeated assessment of patients' liver tissue conditions are impractical. We assessed the 10‐year changes in liver stiffness measurements (LSM) utilizing vibration‐controlled transient elastography in NAFLD patients. Methods: From January 2006 to September 2007, LSM was carried out for 97 biopsy‐proven NAFLD patients. Of these, 34 patients underwent 10‐year LSM reassessments (14 of them with paired biopsies). Results: We evaluated the changes in the fibrosis stage as estimated using LSM (FS‐LSM). Over a 10‐year period, 32.4% had FS‐LSM progression, 50% had static disease, and 17.6% had FS‐LSM improvement. From among the initially diagnosed non‐alcoholic steatohepatitis patients, 18% had progressed to considerable stage 4 (cirrhosis) 10 years later. In this cohort, none of the patients who had been initially diagnosed as FS‐LSM stage 0 had progressed to cirrhosis 10 years later. The changes in LSM were correlated with the change in the histological fibrosis stage, the NAFLD activity score, and the change in the sum of the steatosis, activity, and fibrosis score. Improving more than 1 body mass index (kg/m 2 ) and having a higher initial aspartate aminotransferase, alanine aminotransferase (ALT), or ALT responder (>30% improvement or reduction to less than 40 IU/L) were factors contributing to LSM improvements (≥2 kPa). Conclusions: Vibration‐controlled transient elastography is likely to become a more clinically important tool for the long‐term monitoring of NAFLD patients.